Traditional Ecological Wisdom for the Resilience of Indigenous Peoples in Indonesia - Enkin Asrawijaya (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This paper will discuss how traditional ecological wisdom is invaluable to indigenous peoples in Indonesia because it provides them with techniques for sustainable resource management while at the same time encouraging conservation practices that are rooted in spirituality. The analytical approach will use the concept of Sustainable Practices, thus the importance of this knowledge is not only for preserving indigenous culture but also for achieving long-term environmental sustainability on a global scale. Traditional ecological wisdom refers to the knowledge and practices passed down through generations by indigenous communities. These practices are deeply rooted in a sustainable approach to living in harmony with nature. This understanding guides their sustainable practices, such as rotational farming and fishing techniques that allow for natural regeneration. Throughout history, indigenous communities have developed a deep understanding of land management and agriculture techniques that are rooted in their connection to the natural world. This knowledge has been passed down through generations, allowing indigenous peoples to sustainably cultivate the land and ensure its productivity for future generations.